2017
DOI: 10.1177/0300985817698210
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Aging in NODscidgamma Female Mice

Abstract: In the past decade, NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ (NSG, NOD scid gamma) mice have become a model of choice in several areas of biomedical research; however, comprehensive data on their spontaneous age-related pathology are not currently available in the literature. The prevalence of spontaneous morbidity affecting aged NSG female breeders enrolled in a parasitology study was documented with classification of neoplastic and non-neoplastic (inflammatory, metabolic, degenerative) lesions. Malignant mammary neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 57 publications
1
64
1
Order By: Relevance
“…These findings extend prior reports regarding the utility of PCR testing of IVC exhaust airways as a component of murine health surveillance 2,12,24,31,39,44,45 and are especially applicable to improved health monitoring of immunodeficient mice, in which such agents serve as opportunistic pathogens. 1,5,15,20,56,58,59,74 Although sanitization by mechanized washing reduced the PCR evidence of these microbes, most species (that is, 5 of the 8 obtained) remained PCR-detectable. VHP exposure with equipment left unassembled (that is, in the static-open configuration) did not substantively further reduce the PCR evidence of microbes in exhaust plenums.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings extend prior reports regarding the utility of PCR testing of IVC exhaust airways as a component of murine health surveillance 2,12,24,31,39,44,45 and are especially applicable to improved health monitoring of immunodeficient mice, in which such agents serve as opportunistic pathogens. 1,5,15,20,56,58,59,74 Although sanitization by mechanized washing reduced the PCR evidence of these microbes, most species (that is, 5 of the 8 obtained) remained PCR-detectable. VHP exposure with equipment left unassembled (that is, in the static-open configuration) did not substantively further reduce the PCR evidence of microbes in exhaust plenums.…”
Section: Discussionmentioning
confidence: 99%
“…As immunodeficient and genetically engineered mice comprise an ever larger portion of murine inventories, microbes to be monitored in murine facilities will likely expand to include opportunistic microbes, members of the microbiome, and new, previously unrecognized microbial pathogens. 1,5,6,11,15,[18][19][20]39,40,43,46,56,[58][59][60]62,63,74 We recently demonstrated that active-closed VHP sterilization of secondary housing equipment was an important component to facilitywide eradication of Corynebacterium bovis, 43 perhaps one of the more problematic opportunistic outbreaks in an immunodeficient murine colony. Our prior report described that despite the absence of marked, widespread morbidity attributable to Corynebacterium bovis, this organism can be harbored by a number of immunodeficient strains, is PCR-identifiable among unaffected immunocompetent strains, and is broadly disseminated to all facility areas during an outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodeficient mice are exquisitely sensitive to opportunistic microbes, including members of the microbiome and emerging pathogens. 7,25,26,29 In addition to the obvious potential for morbidity or mortality, one detrimental drawback of even subclinical infections of immunodefi cient mice is the variability induced into research data, normative physiologic responses, and to study metrics, thereby invalidating the fi ndings. 25 When murine studies involve rare, genetically unique human PDX specimens and when experimental therapeutics are available only in limited aliquots, the tolerance for data variability and study invalidation due to opportunistic microbes becomes substantially less.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocystis murina: respiratory disease and mortality in immunodeficient mice. 378,381,[534][535][536] Candida spp. : recent reports associated with immune deficiency/suppression and or use of antimicrobials.…”
Section: Fungimentioning
confidence: 99%